PEMANFAATAN TEKNOLOGI CNC DALAM INOVASI AKSESORIS DAN PART KENDARAAN - Winanto, Heri; Arba, Faza; Syafrudin, Fahri (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2025)
The automotive industry, particularly in the motorcycle sector, is experiencing significant growth, accompanied by increasing demand for variation and customization among consumers. CNC (Computer Numerical Control) technology enables high-precision manufacturing, time efficiency, and design flexibility—key factors in creating innovative and customized products. This article discusses how CNC technology is utilized in the design, production, and modification processes of vehicle accessories and parts, including the challenges and opportunities involved in its implementation. The study is based on direct observation of the design and initial planning process, CNC programming, manufacturing, and testing. The results show that CNC has a positive impact on the automotive industry. It not only enhances production efficiency and precision but also drives innovation in vehicle component design.